1999
DOI: 10.1097/00003246-199910000-00026
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of low-molecular-weight heparin (dalteparin) versus unfractionated heparin as anticoagulant during continuous venovenous hemodialysis with filtration

Abstract: Fixed-dose dalteparin provided identical filter life, comparable safety, but increased total daily cost compared with adjusted-dose heparin. Unfractionated heparin remains our anticoagulant of choice for continuous hemofiltration in intensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
1
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(59 citation statements)
references
References 14 publications
5
44
1
9
Order By: Relevance
“…No major bleeding occurred, but 26% of the patients in the enoxaparin group had minor bleeding episodes. This finding differs from the report by Reeves et al 30 and by Joannidis et al 35 who found no difference in the prevalence of hemorrhagic complications between the two methods of anticoagulation.…”
Section: Enoxaparin Vs Unfractioned Heparin In Cvvhd 325contrasting
confidence: 99%
See 4 more Smart Citations
“…No major bleeding occurred, but 26% of the patients in the enoxaparin group had minor bleeding episodes. This finding differs from the report by Reeves et al 30 and by Joannidis et al 35 who found no difference in the prevalence of hemorrhagic complications between the two methods of anticoagulation.…”
Section: Enoxaparin Vs Unfractioned Heparin In Cvvhd 325contrasting
confidence: 99%
“…At 48 hours of CVVHD, platelet count and proportion of patients with thrombocytopenia were similar between enoxaparin and UFH groups in accordance with the data reported by Reeves et al 30 Nevertheless, in patients who presented bleeding, platelet levels tended to be lower. It is probable that thrombocytopenia in this context was associated more with severity of disease (sepsis and multiple organ dysfunction syndrome) than to an autoimmune effect induced by enoxaparin (heparin-induced thrombocytopenia), because it occurred earlier than 4 days and was not accompanied by thromboembolic events.…”
Section: Enoxaparin Vs Unfractioned Heparin In Cvvhd 325supporting
confidence: 90%
See 3 more Smart Citations